Exploitation of Inland-Breeding Antarctic Petrels by South Polar Skuas - Brooke, Michael de L; Keith, Dave; Røv, Nils (Oecologia, 1999)
During the austral summer of 1996/1997 we studied south polar skuas at Svarthamaren, Dronning Maud Land, Antarctica, where the world's largest known colony of Antarctic petrels is found. Our censuses suggested approximately 250 full-grown skuas and 140,000 breeding pairs of petrels were present. During their breeding season, skuas did not visit the open sea at least 200 km from the site; they relied entirely on prey caught and scavenged from the petrel colony. Because the site is so isolated, we asked whether the prey (petrels) had swamped the predators (skuas), or whether there was evidence that predator numbers were limited by the size of the prey population. Particularly at the end of the petrel incubation period, we found a close correspondence between the energy required by adult skuas and their chicks, ascertained from time budget studies, and the rate at which petrel eggs disappeared from the colony. This suggests that, in this closed system, the predator population was limited by the prey population, and that predator swamping was not an advantage that petrels gained by nesting in this remote location.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

The influence of ornithogenic products on the nutrient status of soils surrounding nests on nunataks in Dronning Maud Land, Antarctica - Cocks, Martin P; Harris, Jean M; Steele, William K; Balfour, Dave A (Polar Research, 1999)
Keywords: Dronning Maud Land; fugler; nunataker; næringsstoff; ornitologi; petreller

Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Variability in snow layering and snow chemistry in the vicinity of two drill sites in western Dronning Maud Land, Antarctica - Hansson, Margareta; Holmlund, Per; Karlöf, Lars; Stenberg, Malin (Annals of Glaciology, 1999)
As part of the pre-site survey in Dronning Maud Land for the European Project for Ice Goring in Antarctica (EPICA), the spatial variability of snow-layer thickness and snow chemistry was studied at two geographically different ice-core drill sites. The study aimed to quantify error bars on accumulation rates derived from firn and ice cores. One site is located on the polar plateau at Amundsenisen (76° S, 8° W) and the other in the coastal area at Maudheimvidda (73° S, 13° W). Medium-deep ice cores (100 m) and shallow firn cores (10-20 m) were drilled and snow pits (0.5-2 5 m) were dug at each site. At Amundsenisen a large (16 m x 6 m x 2.5 m deep) snow pit was dug. Snow structure in this large snow pit was mapped using optical surveying equipment, and photographically documented. Samples for analysis of nine ions and oxygen isotopes were collected along one depth profile. Density and in situ electrical conductivity measurements were made along three depth profiles! Snow-layer variability was studied in two different areas and at two different scales. At a regional scale, measured by snow-radar soundings, the variability was 8% on the polar plateau and 45% in the coastal area. The variability at a micro-scale in the large snow pit was 9%. The results indicate that ice cores from the polar plateau are more representative for a larger area than ice cores drilled in the coastal area There is no doubt that there are significant error bars on high-resolution accumulation data received from firn and ice cores, especially from the coastal area, but averaging over tens of years reduces the error in accumulation estimates.
Keywords: Dronning Maud Land; fysisk geografi; geokjemi; glasiologi; iskjerner; paleoklimatologi

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Diet and prey consumption of Antarctic petrels Thalassoica antarctica at Svarthamaren, Dronning Maud Land, and at sea outside the colony - Lorentsen, Svein-Håkon; Klages, Norbert; Røv, Nils (Polar Biology, 1998)
The diet of the Antarctic petrel Thalassoica antarctica was studied during two seasons at Svarthamaren, an inland colony in Dronning Maud Land, Antarctica, and in the pack ice off the coast of Svarthamaren. The most important food (wet mass) at Svarthamaren was crustaceans (67%), fish (29%) and squid (5%); however, individuals collected in the pack ice took mostly fish (87%). The prey composition and lengths of prey are comparable to what has been documented in other studies on this species. Estimates of food consumption by birds breeding at Svarthamaren (ca. 250,000 pairs) suggest that approximately 6500 tonnes of crustaceans, 2800 tonnes of fish and 435 tonnes of squid are consumed during the breeding season. The annual consumptions of these birds are estimated to be 34,100 tonnes of crustaceans, 14,700 tonnes of fish, and 2300 tonnes of squid. Satellite telemetry data indicate that Antarctic petrels from Svarthamaren may fly more than 3000 km during one foraging trip, and thus may cover a huge ocean area to obtain their prey.
Keywords: Dronning Maud Land; NARE 1991/92; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Regulation of food provisioning in the Antarctic petrel; the importance of parental body condition and chick body mass - Tveraa, Torkild; Sether, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Journal of Animal Ecology, 1998)
1. Two hypotheses may explain how long-lived seabirds regulate the food provisioning to their chick. The fixed level of investment hypothesis states that the parents provide food for their chick according to an intrinsic rhythm, independent of their chick's need. The flexible investment hypothesis states that the parents adjust their food provisioning both according to their chick's and their own need. 2. We tested how the Antarctic petrels adjust the food-provisioning according to their own body condition or to their chick's need. First, we selected parents in poor and good body condition. Then we gave all parents randomly a chick of different body mass, but of the same age. We then measured the chicks daily until they were fed for the first time after swapping. 3. Parents in good body condition at hatching were more likely to produce a chick that was still alive 9 days after hatching than parents in poor body condition. Chick body mass at day 9 and at the end of the guarding period was positively related to the mean body condition of the parents at hatching. 4. The meal size provided by parents in good body condition was larger than that provided by parents in poor body condition. Parents in good body condition delivered more food to small than to large chicks, whereas no such relationship was found among parents in poor body condition. 5. Our results suggest that the Antarctic petrel parents adjust the amount of food delivered to their chick according to both the chick's need and their own body condition, and that the ability to respond to the chick's need is dependent upon their own body condition.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Body mass and parental decisions in the Antarctic petrel Thalassoica antarctica : how long should the parents guard the chick? - Tveraa, Torkild; Sæther, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Behavioral Ecology and Sociobiology, 1998)
In Procellariiformes, the parents guard the chick after it has attained homeothermy. This strategy may reduce the probability that a small chick is taken by predators, but is costly as only one parent can forage at a time. The decision to leave the chick may therefore be a compromise between the chick's vulnerability to predators, the body condition of the parent on the nest and whether the foraging parent returns in time. We studied how the number of days that parents guarded the chick was related to the body mass of the parent at the nest and the time the foraging parent spent at sea in the Antarctic petrel Thalassoica antarctica. We also examined how the body mass of the parent on the nest and the duration of the foraging trips influenced the chicks' body condition at the end of the guarding period. When the foraging parent did not return to the nest in time to relieve its mate, the number of days the parent on the nest kept guarding the chick was positively related to its body mass on arrival in the colony. The number of days the foraging parent spent at sea was positively related to the body mass of its mate, but those that returned in time had a shorter stay at sea relative to their mate's body mass than those that did not return before their mate had left. Apparently, both the body mass of the parent at the nest and the ability of the foraging parent to adjust its stay at sea to the mate's body mass is important for the number of days the parents guard the chick and also the chick's body condition at this point. The inability to return to the nest before the mate has left may be the result of needing a minimum amount of time at sea to find food, or because some parents having low foraging success and therefore prolong their stay at sea.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Geological observations in Gjelsvikfjella, Mühlig-Hogmanfjella and western Orvinfjella during NARE 96/97 - Austrheim, Håkon; Elvevold, Synnøve; Engvik, Ane K; Paulsson, Oskar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geologi

Geodetic measurements in Dronning Maud Land - Barstad, Bjørn; Eiken, Trond; Finnes, Randi; Øvstedal, Ola (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geodesi; målinger

Geodetic and topographic work - Barstad, Bjørn; Eiken, Trond; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; geodesi; topografi

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Distribution and food consumption of crabeater seals off Dronning Maud Land - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; seler; zoologi

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Effects of Egg Size and Parental Quality on Early Nestling Growth: An Experiment with the Antarctic Petrel - Amundsen, Trond; Lorentsen, Svein-Hakon; Tveraa, Torkild (Journal of Animal Ecology, 1996)
A large number of studies have reported a positive relationship between the egg size of birds and the subsequent growth and/or survival of nestlings, but such effects may partly be due to confounding variables, e.g. parental quality. In order to evaluate the potential effects of egg size, and of parental quality, on early nestling growth in the Antarctic petrel, we performed an experiment in which eggs of different size were swapped between nests. 2. From a sample of 300 nests with eggs of known size, we selected eggs belonging to the lower quartile (small eggs), and those belonging to the upper quartile (large eggs), with respect to volume. Half of the small eggs were exchanged with small eggs from other nests, and the other half with large eggs. A similar procedure was used for large eggs. Growth and survival of the nestlings were recorded until 12 days old. 3. Hatching success was positively related to egg size. 4. Egg size influenced nestling body mass until the age of 3 days, and tarsus length was affected until 12 days old. However, these effects were not due to an effect of egg size on growth rates, but reflected instead the influence of egg size on hatchling size. 5. In contrast to most previous studies, we found no effect of parental quality (as reflected in the size of own eggs) on foster nestling size or growth until 12 days old. This could be because egg size does not reliably reflect parental quality in the species, or because parental effects become evident only at later nestling stages. 6. We discuss why egg size variation is maintained in this and other species where egg size influences parental fitness through the survival of eggs or nestlings.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

A century of accumulation and temperature changes in Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Gundestrup, Niels; Mayewski, Paul; Whitlow, Sallie; Twickler, Mark (Journal of Geophysical Research: Atmospheres, 1996)
Keywords: Dronning Maud Land; akkumulasjon; klima; målinger; snø; temperatur

Regulation of Food Provisioning in the Antarctic Petrel Thalassoica antarctica - Lorentsen, Svein-Håkon (Journal of Animal Ecology, 1996)
1. Life-history theory predicts that individual birds should invest in reproduction according to their current body condition and the future prospects for survival and reproduction. Thus, it could be expected that current adult body condition should significantly influence food provisioning rates, food loads and concurrent chick growth in the Antarctic petrel. 2. In order to study the significance of parental body condition I correlated meal sizes, feeding frequencies and chick growth with the body condition of the parents. 3. There was a strong correlation between the average meal size delivered to a chick and its growth rate. Adult body condition at the time of hatching was strongly correlated with the average size of meals delivered to individual chicks. Male and female body condition at the time of hatching and average body condition of the pair at the first incubation shift and at hatching significantly influenced the body mass of the chick on day 30. Male body condition and the average body condition of the pair correlated significantly with the growth rate of the chick. 4. The difference in body mass at the age of 30 days of chicks from parents with good body condition compared with chicks from parents with poorer body condition was nearly double that expected. 5. The results strongly suggest that the effort spent during the chick-rearing period, and thus reproductive success, is regulated by the body condition of the parents.
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi

Egg Size and Early Nestling Growth in the Snow Petrel - Amundsen, Trond (The Condor, 1995)
I studied egg size variation, and the influence of egg size on early nestling growth, in Snow Petrels Pagodroma nivea breeding at Svarthamaren, Dronning Maud Land, Antarctica (71 degrees 53'S, 5 degrees 10'E). Egg sizes ranged from 36.4 to 52.1 cm(3), with a mean of 44.9 cm(3). Hatching occurred during 16-24 January, with a median hatching date of 20 January. Egg size had a significant effect on the body mass of hatchlings, explaining 30% of the variation in body mass of nestlings hatched within the last 24 hr, and 58% of the body mass variation of nestlings weighed while still slightly wet. An experiment, which included swapping of eggs between nests, together with analyses of non-manipulated nests, revealed an effect of egg size on nestling body masses at ages of two and four days. From the experiment, no effect of maternal quality as expressed by her egg size could be found. At an age of four days, 40% of the nestlings were left alone in the nest by their parents. Nestlings not attended by a parent at this age were significantly lighter than were those with parental company. Parents that had left their young by the time these were four days old may have been poor quality birds, as indicated by the tendency for such birds to have laid smaller eggs than had those still tending their young at the same nestling age.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of parental investment in the Antarctic petrel Thalassoica antarctica: an exchange experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Polar Biology, 1995)
An experiment was conducted on the Antarctic petrel to test whether the parents were able to respond to changes in food demand of their offspring. Two experimental groups were formed by replacing eight 20-day-old chicks with 10-day-old chicks, and vice versa. The growth rate of chicks in the experimental groups was compared with that in two control groups with chicks of known age. The growth rate of 10-day-old chicks in the nests of parents which initially had 20-day-old chicks did not differ significantly from that in their respective control groups. This indicates that those parents were able to raise a new young nestling, despite having already raised another chick from hatching to 20 days. However, the 20-day-old chicks placed in nests with 10-day-old chicks had a significantly lower growth rate than their control group. Feeding rate per day and nest did not differ significantly among any of the groups. This suggests that the observed difference in growth rate between 20-day-old chicks is related to a lower amount of food delivered per visit to experimental chicks. Thus, in the Antarctic petrel, the feeding rate apparently is not regulated by the status of the chick, but by the parents' ability to gather food or willingness to provide food for the chicks.
Keywords: Dronning Maud Land; NARE 1989/90; fugler; ornitologi; petreller; zoologi

Incubation and brooding performance of the Antarctic Petrel Thalassoica antarctica at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils (Ibis, 1995)
Antarctic Petrel Thalassoica antarctica incubation and brooding effort was studied at Svarthamaren, Dronning Maud Land, during the austral summer of 1991-1992. The females probably left the nest site shortly after egg laying. The duration of incubation and brooding shifts as well as the daily weight loss (absolute and proportionate) were comparable with those of other similar-sized procellariform species. Males spent more time incubating and brooding than did females, suggesting higher female energy stress due to egg laying, Incubating birds which were below average weight were likely to desert the nests before their mates returned from feeding trips. Both males and females lost approximately one-fifth of their body-weight during their first incubation shifts. Nevertheless, they increased their initial weights from egg laying to hatching and had their highest initial weights when they returned to start the shift during which the egg hatched. No factors related to adult body-weight explained the duration of the incubation shifts, Both males and females gained weight at a higher rate when at sea than they lost it during incubation, and it is suggested that factors unrelated to food availability or individual feeding skills may be important in regulating the duration of the incubation shifts and the stay at sea.
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Spatial and temporal patterns in snow accumulation, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Journal of Glaciology, 1994)
During the Swedish Antarctic Expedition to Dronning Maud Land, Antarctica, 1988–89 the net accumulation was estimated for an area from the coast to about 400 km inland. Stake measurements were used to obtain the spatial variability and firn cores were used for the temporal variability. The mean annual accumulation for the period 1976–88 is about 0.4mw.e. for Riiser-Larsenisen and about 0.3mw.e. for the area above the grounding line. The accumulation rate at higher altitudes, > 2500 m a.s.1., is about 0.1 m w.e. for 1955–88. One record from the ice shelf covers the period 1957–88, and suggests an increase in accumulation of about 12%. Between 1976 and 1988, the accumulation has decreased by about 50%, most likely due to lower temperatures as suggested by the temperature record from Halley.
Keywords: Dronning Maud Land; glasiologi

Sex determination of Antarctic Petrels Thalassoica antarctica by discriminant analysis of morphometric characters - Lorentsen, Svein-Håkon; Røv, Nils (Polar Biology, 1994)
We present data on sexual dimorphism in some morphological measurements (wing length, head length, bill depth and bill length) in the Antarctic Petrel Thalassoica antarctica. Males were on average larger than females for all measurements. Sexual dimorphism was on average largest for bill depths whereas wing lengths discriminated least between the sexes. A discriminant function including bill depth, head length and wing length correctly sexed 92% of the sample. Due to between-measurer variation it is recommended that morphometric measurements obtained by others on sexed birds are compared with ours before proceeding with the use of the discriminant function on unsexed individuals.
Keywords: Dronning Maud Land; NARE 1991/92; biodiversitet; fugler; ornitologi; zoologi; økologi

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Seabird studies at Svarthamaren, Dronning Maud Land - Røv, Nils; Lorentsen, Svein-Håkon; Bangjord, Georg (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi

Dronning Maud Land - Tollefsen, Ivar (Mortensen, 1994)
Keywords: Dronning Maud Land; Sydpolen; ekspedisjoner; fjellklatring; polarekspedisjoner

Spectral bi-directional reflectance of snow and glacier ice measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1994)
Visible and near-infrared spectral reflectances of snow and superimposed ice were measured in Dronning Maud Land, Antarctica, during the 1992-93 austral summer. Spectral-reflectance curves of both snow and superimposed ice remain high ( > 80%) in the visible region. A pronounced decrease in reflectance appears in the near-infrared, especially for superimposed ice. Superimposed ice with a 1 cm thick surface layer of ice-bound snow crystals had a considerably higher reflectance than superimposed ice containing only a few snow crystals. Furthermore, these data prove that snow and superimposed ice reflect solar radiation specularly and suggest that the anisotropy strengthens with increasing wavelengths. Integrated in-situ reflectances corresponding to Landsat TM bands 1-4 show that TM band 1 is least affected, whereas TM band 4 is most affected by anisotropy. Furthermore, the anisotropy increases with increasing off-nadir viewing angles up to an angle corresponding to 90°-θs (θs = solar elevation). For a 15° off-nadir sensor-observation angle, the average snow reflectance for TM bands 1--4 is about 10% higher than at nadir. Similarly, the apparent reflectance can be more than 50% higher than the nadir reflectance for larger observation angles. Consequently, if satellite-derived reflectances are going to be considered as absolute values, a topographic-correction model is needed to correct for the effects of anisotropy.
Keywords: Dronning Maud Land; glasiologi

Granulites and garnet–cordierite gneisses from Dronning Maud Land, Antarctica - Bucher-Nurminen, Kurt; Ohta, Yoshihide (Journal of Metamorphic Geology, 1993)
The central sector of Mühlig-Hofmannfjellet (3°E/71°S) in western Dronning Maud Land (East Antarctic shield) is dominated by large intrusive bodies of predominantly orthopyroxene-bearing quartz syenites (charnockites). Metasedimentary rocks are rare; however, two distinct areas with banded gneiss–marble–quartzite sequences of sedimentary origin were found during the Norwegian Antarctic Research Expedition NARE 1989/90. Cordierite-bearing metapelitic gneisses from two different localities contain the characteristic mineral assemblage: cordierite + garnet + biotite + K-feldspar + plagioclase + quartz ± sillimanite ± spinel. Thermobarometry indicates equilibration conditions of about 650°C and 4 kbar. Associated orthopyroxene–garnet granulites, on the other hand, revealed pressures of about 8 kbar and temperatures of 750°C. The earlier granulite facies metamorphism is not well preserved in the cordierite gneisses as a result of excess K-feldspar combined with interaction with an H2O-rich fluid phase, probably released by the cooling intrusives. These two features allowed the original high-grade K-feldspar + garnet assemblages to recrystallize as cordierite–biotite–sillimanite gneisses, completely re-equilibrating them. Phase relationships indicate that the younger metamorphic event occurred in the presence of a fluid phase that varied in composition between the lithologies.
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geologi

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Thermoregulatory abilities in chicks of the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (Polar Biology, 1991)
We studied the thermoregulatory capacity of Antarctic Petrel chicks, Thalassoica antarctica, breeding in a large colony in Queen Maud Land (71-degrees-53'S, 5-degrees-10'E) on the Antarctic continent. Compared to newly hatched chicks of other birds, those of the Antarctic Petrel are characterized by a relatively high standard metabolic rate (SMR) and thermal conductance. Their metabolic scope is limited, however, being only 1.6 times the SMR, and they consequently depend on parental brooding to maintain T(b). At an age of 11 days the chicks become thermally independent and are left alone in the nest. The chicks keep a relatively high body temperature (> 36-degrees-C) throughout their early development and we found no indication that they normally experience hypothermia. A significant positive relationship between latitude of breeding and SMR of the hatchlings is shown to exist for procellariiform birds. It is suggested that the high SMR found in Antarctic Petrel hatchlings could be a prerequisite for achieving a high growth rate, rather than being of any thermoregulatory significance.
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; petreller; zoologi

Humoral-immunologiske endringar ved korttidsisolasjon i Antarktis - Molvær, Otto Inge; Matre, Roald; Bendiksen, Fredrik S; Reitehaug, Per-Ivar; Hjelle, John O (Norwegian Antarctic Research Expeditions 1989-1990, 1991)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; immunologi; mikrobiologi

Antarktispetrellen: på grensen av det mulige - Sæther, Bernt-Erik (Naturen, 1991)
Keywords: Dronning Maud Land; fugler; ornitologi

Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geology around the Norwegian Antarctic station "Troll", Jutulsessen, Dronning Maud Land - Dallmann, Winfried K; Austrheim, Håkon; Bucher-Nurminen, Kurt; Ohta, Yoshihide (Norsk Polarinstitutt, 1990)
During the Norwegian Antarctic Research Expedition 1989/90, a pennanent, unmanned research station was raised in Jutulsessen, Gjelsvikfjella, western Dronning Maud Land. The present report is a description of the geology of the area accessable from the station. Exposures of rocks in this part of Dronning Maud Land are restricted to a coastal mountain chain at c. 200-250 km distance from the ice shelf edge at elevations between 1000 and 3000 m. Quaternary deposits are particularly restricted to the inner parts of the Jutulsessen glaeier cirques. Deposits are till and talus which locally are admixing at slope angles of c. 25°. Moraines are poorly developed. Patterned ground ('stone pits') are common at slope angles below c. 15°. Recently active phenomena of special interest are ice-margin meltwater lakes with pingo-like 'blisters " the deep frost-shattering all over the mountain walls and hoIes in rock surfaces as a result of wind activity with grinding particles. The bedrock belongs to the East Antarctic craton. The area under consideration (western Miihlig-Hofmannfjella and Gjelsvikfjella) consists of high-grade metamorphic rocks and fonns one of the world's best exposed granulite terranes. Orthogneisses and minor metasediments have been intruded by a series of charnockites, partly altered to granulites (the 'Svarthamaren charnockite complex'), and a sequence of dyke rocks. Migmatization has affected large parts of the gneisses. Both gneisses and granulites/charnockites show abundant evidence of transition from granulite to amphibolite facies and vice versa, and the important role of fluid-rock interactions leading to these processes can be studied. The gneisses at Jutulsessen show a complex defonnation history. They are thought to be derived from granitic intrusions, though minor amounts of high-grade metamorphic, metapelitic gneisses may represent their original host rocks. Early tectonism (c. 1000-1200 m.y.) produced gneissosity, compositional banding and a leucosome phase under high-grade metamorphic conditions. This was followed by multiple and complex intrusive activity, partial migmatization and a tectonic overprint with abundant shear defonnation under amphibolite-facies conditions (c. 450-500 m.y.).
Keywords: Dronning Maud Land; NARE 1989/90; berggrunnsgeologi; geologi

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella, Dronning Maud Land, east Antarctica - Ohta, Yoshihide; Tørudbakken, Bjørn; Shiraishi, Kazuyuki (Polar Research, 1990)
As a part of the Norwegian Antarctic Research Expedition 1984/85, geological mapping was performed in Gjelsvikfjella and western Muhlig-Hofmannfjella, Dronning Maud Land. The northern part of Gjelsvikfjella is dominated by the Jutulsessen metasupracrustals which have been intruded by a major gabbroic body and several generations of dykes. To the south the metasupracrustals gradually transform into the Risemedet migmatites. In western Muhlig-Hofmannfjella the bedrock is dominated by the large Svarthamaren Charnockite batholith. The batholith is bordered by the Snotoa metamorphic complex outcropping to the south and west in Muhlig-Hofmannfjella and it is characterized by a high content of partly assimilated country rock inclusions. Mineral paragenesis and geothermometry/geobarometry suggest a two-stage tectonothermal-igneous history with an initial intermediate pressure, upper amphibolite to granulite facies metamorphism followed by high temperature transformations related to the charnockite intrusion. The age of the initial tectonothermal event is probably about 1,100 Ma. Geochronological work in the present study (Rb/Sr whole rock) gave an age of 500 +/- 24 Ma for the Svarthamaren Charnockite, interpreted to record the age of crystallization. Late brittle faulting and undeformed dolerite dykes outcropping in Jutulsessen are believed to be related to Mesozoic crustal stretching in the Jutulstraumen-Pencksokket Rift Zone to the west.
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

Satellittkartlegging ved Norsk Polarinstitutt - Amlien, Jostein (Kart og plan, 1989)
Keywords: Dronning Maud Land; fotogrammetri; kartlegging; kartografi; satellite bilder

Miljøspørsmål i fokus: forskningsskipet "Andenes" på vei mot Antarktis - Friberg, Fred (Svalbardposten, 1989)
Keywords: Dronning Maud Land; ekspedisjoner

Place-names of Heimefrontfjella and Lingetoppane, Dronning Maud Land, Antarctica - Gjelsvik, Tore (1989)
Keywords: Dronning Maud Land; stedsnavn

Microclimates and water budget of algae, lichens and a moss on some nunataks in Queen Maud Land - Gjessing, Yngvar; Øvstedal, Dag Olav (International Journal of Biometeorology, 1989)
Keywords: Dronning Maud Land; NARE 1984/85; alger; biologi; lav; mikroklima; moser; planter

Anomalous palaeomagnetic directions in a Mesozoic basaltic dyke; arguments for fault-induced remagnetization - Løvlie, Reidar; Mitchell, John (Physics of the earth and planetary interiors, 1989)
Anomalously steep palaeomagnetic directions from the central part of an ∼ 5 m wide basaltic dyke from Fossilryggen, East Antarctica, suggest a Recent to late Tertiary age for its remanent magnetization, in conflict with KAr isotope ages of 162 ± 4 and 217 ± 3 Ma obtained from the central and slickenside margins respectively. Three neighbouring basaltic intrusions carry stable magnetizations whose directions (mean D, 23°; mean I, −40° and pole position, 38°N, 40°E) accord with previously obtained Mesozoic results from lava flows in the Vestfjella basalt province, East Antarctica. Rock magnetic properties do not discriminate between the different dykes, and it is proposed that the anomalous directions represent spot-readings of the geomagnetic field which arise from complete remagnetization during a period of faulting in Recent to late Tertiary times.
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; geofysikk; geologi

Establishment of Troll, a new station facility for summer operations: initial environmental evaluation - Polarinstitutt, Norsk (Norsk Polarinstitutt, 1989)
Keywords: Dronning Maud Land; Norge; forskningsstasjoner; miljøspørsmål; polarforskning

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Tekstur-estimering på LANDSAT-5 MSS opptak fra Antarktis - Albregtsen, Fritz (Proceedings fra NOBIM-konferansen 1988: Nordisk konferanse om bildebehandling og mønstergjenkjenning, Oslo, 2-3 juni 1988, 1988)
Keywords: Dronning Maud Land; informatikk; is; satellite bilder; snø

Muscicolous Lepraria species and other leprarioid lichens in the Antarctic - Botnen, Astri; Øvstedal, Dag Olav (Polar Research, 1988)
Keywords: Dronning Maud Land; botanikk; forskning; lav; planter

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Census of breeding Antarctic petrels Thalassoica antarctica and physical features of the breeding colony at Svarthamaren, Dronning Maud Land, with notes on breeding snow petrels Pagodroma nivea and south polar skuas Catharacta maccormicki - Mehlum, Fridtjof; Gjessing, Yngvar; Haftorn, Svein; Bech, Claus (Polar Research, 1988)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

Numerical Analysis of Landsat Thematic Mapper Images of Antarctica: Surface Temperatures and Physical Properties - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1988)
Keywords: Dronning Maud Land; glasiologi; innlandsis; satellittbilder; topografi

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Botany of two Antarctic mountain ranges: Gjelsvikfjella and Mühlig-Hofmannfjella, Dronning Maud Land. I. General ecology and development of the Antarctic cold desert cryptogam formation - Engelskjøn, Torstein (Polar Research, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; forskning; planter

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Flow and thickness of Riiser-Larsenisen, Antarctica - Orheim, Olav; Drewry, David (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Lichens and lichen parasites from the British-Swedish-Norwegian antarctic expedition 1949-52 to Dronning Maud Land - Øvstedal, Dag Olav (Cryptogamie: bryologie, lichenologie, 1986)
Keywords: Dronning Maud Land; botanikk; ekspedisjoner; lav; parasitter; planter

Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Geodetic-topographic measurements in Dronning Maud Land and on Bouvetøya - Eiken, Trond; Svendsen, Knut (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geodesi; målinger; topografi

Botany of Gjelsvikfjella and Muhlig-Hofmannfjella, Dronning Maud Land - Engelskjøn, Torstein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; planter

Geological and palaeomagnetic research in Vestfjella Dronning Maud Land - Furnes, Harald; Løvlie, Reidar (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Meteorological and glaciological studies in Dronning Maud Land - Gjessing, Yngvar (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; glasiologi; meteorologi

Geomorphological and glaciological observations in Vestfjella, Dronning Maud Land - Jonsson, Stig (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geomorfologi; glasiologi

Ornithological investigations in Mühlig-Hofmannfjella, Dronning Maud Land - Mehlum, Fridtjof; Bech, Claus; Haftorn, Svein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; zoologi

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella - Ohta, Yoshihide; Tørudbakken, Bjøn (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geologi

Sedimentological research in northwestern part of Dronning Maud Land - Olaussen, Snorre (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geologi; nunataker; sedimentologi

Terrestrial invertebrates of Mühlig-Hofmannfjella, Dronning Maud Land - Sømme, Lauritz (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; leddyr; virvelløse dyr; zoologi

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Snorre til Sydpolen: 38 dager på isen (Status (Statoil), 1984)
Keywords: Dronning Maud Land; ekspedisjoner; geologi

Marine and non-marine contribution to the chemical composition of snow at the Riiser-Larsenisen Ice Shelf in Antarctica - Gjessing, Yngvar (Atmospheric Environment (1967), 1984)
The distribution with depth of seven different ions in three snow profiles, 1, 60 and 120km from the coast on Riiser-Larsenisen Ice Shelf (72° 30′ S, 15°E) shows a close co-variation between ions of marine origin and non-correlation between these ions and ions of presumptively non-marine origin. The deposition rates of ions of marine origin vary as 50:1 over some 120 km distance from the coast. The SO42−Na+ ratio in snow near the coast is lower than for bulk sea water indicating a loss of SO42− in snow to the atmosphere by volatilization.
Keywords: Dronning Maud Land; geofysikk; geokjemi; isshelf; meteorologi

Some lichens from Vestfjella, Dronning Mauds Land, Antarctis - Øvstedal, Dag Olav (Cryptogamie. Bryologie, lichénologie, 1983)
Keywords: Dronning Maud Land; botanikk; lav; planter

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Petrology and geochemistry of Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica - Furnes, Herald; Neumann, Else-Ragnhild; Sundvoll, Bjørn (Lithos, 1982)
Mineral and whole rocks analyses of 12 Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica, are presented, and their genesis discussed. On the basis of major oxides and norms the basalts may be classified as olivine and quartz tholeiites. Plotted in the Plag Cpx (Opx + 4Q) and Ol Plag Q projections, the compositions are most compatible with fractional crystallization of olivine, clinopyroxene and plagioclase from a basalt liquid at very low pressure. The ratios between strongly incompatible elements such as Rb, Cs, Zr, Hf, Ta and Th vary considerably, and petrographic mixing calculations give poor fits with respect to Rb, Cs, Ta, Th and light REE. Initial 87Sr/86 Sr ratios range between 0.70347 and 0.70687, and show no correlation with Rb/Sr or any other SIE ratios. The trace element and Sr isotope data thus do not suggest any simple cogenetic petrogenetic model. It is concluded that the basalt melts most plausibly have been contaminated by, or mixed with anatectic melts of crustal material, rather than reflecting mantle heterogeneity.
Keywords: Dronning Maud Land; geokjemi; geologi; petrologi

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal of the Royal Astronomical Society, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.
Keywords: Dronning Maud Land; NARE 1976/77; geofysikk; geologi

Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Age relationships of Mesozoic basalt lava and dykes in Vestfjella, Dronning Maud Land, Antarctica - Furnes, Harald; Mitchell, John G (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geokjemi; geologi; petrografi; vulkaner

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Results from Norwegian Antarctic research 1974-1977 - Polarinstitutt, Norsk (1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Norge i Antarktis - Børde, Haakon (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1977)
Keywords: Antarktis; Antarktistraktaten; Dronning Maud Land; historie; internasjonal; politikk

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Preliminary report of the 1976-1977 Norwegian Antarctic Research Expedition - Orheim, Olav (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; M/V Polarsirkel; NARE 1976/77; Weddellhavet; marin geofysikk; oseanografi

Observations on the snow petrel (Pagodroma nivea) in Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norsk Polarinstitutt. Årbok 1976, 1977)
Keywords: Dronning Maud Land; fugler; ornitologi; zoologi

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sarkofagen: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Some observations on the geology of H. U. Sverdrupfjella, Dronning Maud Land - Hjelle, Audun (Norsk Polarinstitutt. Årbok 1972, 1974)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; stratigrafi

Schirmacheroasen: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Starheimtind: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

Diurnal variations of the surface wind over the Antarctic ice shelf - Hisdal, Vidar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

Diurnal wind variations in Antarctica - Hisdal, Vidar (Quarterly Journal of the Royal Meteorological Society, 1972)
For the three Antarctic ice shelf stations considered (Norway Station, Maudheim, and Halley Bay) it is shown that from spring to autumn a systematic diurnal variation of the mean vector wind at the surface exists. Different factors that may be responsible for this variation are discussed. The results seem to agree well with the assumption that in areas far from the ice front (the seaward edge of the ice shelf) the main cause is the larger net gain of momentum in the lowest layers during the middle of the day, while closer to the ice front there is an additional effect of the varying contrast between the air temperature over the sea and over the ice shelf.
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi

Lichens from Vestfjella, Dronning Maud Land - Lindsay, Denis Christopher (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; botanikk; lav; planter

The Norwegian Antarctic Expedition 1970-1971 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1970-71; biologi; geologi; glasiologi

Enorme rikdommer skjult i norsk Antarktis? - Fisksdal, Jan (Nå, 1971)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; mineraler; ressurser

Norge og Antarktis - Tønnessen, Johan Nicolay (Historisk tidsskrift, 1971)
Keywords: Antarktis; Dronning Maud Land; historie; litteratur

The Norwegian Antarctic Expedition 1968-69 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1968, 1970)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1968-69; biologi; geologi; glasiologi

The turbulent transfer over an Antarctic ice shelf - Vinje, Torgny E. (Norsk Polarinstitutt, 1969)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; glasiologi; isshelf

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi

Humboldtfjella: Fimbulheimen (Norsk Polarinstitutt, 1968)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Wohlthatmassivet: Fimbulheimen (Norsk Polarinstitutt, 1968)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Studies of surface snow at Plateau station - Lunde, Torbjørn (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; ekspedisjoner; firnsnø; forskning; glasiologi; metamorfologi; morfologi; snø; stratigrafi

Studies of surface snow at Plateau Station - Orheim, Olav (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; glasiologi; snø; stratigrafi

Surface snow metamorphosis on the Antarctic Plateau - Orheim, Olav (Norsk Polarinstitutt. Årbok 1966, 1968)
Keywords: Dronning Maud Land; firnsnø; glasiologi; metamorfologi; stratigrafi

I telt på evig is: norsk polarekspedisjon til sydpollandet - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; forskning; politikk

Norsk polarekspedisjon til sydpollandet: i telt på evig is - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Dronning Maud Land; ekspedisjoner

Some results of micrometeorological measurements in Antarctica - Vinje, Torgny E (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1967)
Keywords: Dronning Maud Land; glasiologi; meteorologi

What is "Mumiyo" from Antarctica - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1967, 1967)
Keywords: Dronning Maud Land; ekspedisjoner; farmakologi; fugler; ornitologi; zoologi

Filchnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

On the tides at Norway Station and adjacent coastal areas of Antarctica - Hisdal, Vidar (Norsk Polarinstitutt. Skrifter, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; forskning; isshelf; observasjoner; oseanografi; tidevann

On the firn temperatures and glacier flow in Dronning Maud Land - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Dronning Maud Land; firnsnø; glasiologi; isbreer; isstrøm

Annen etappe av Dronning Maud Land Traversen - Orheim, Olav (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; glasiologi; gravimetri; meteorologi; seismologi

Climatological tables for Norway Station (70°30' S, 2°32' W) - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; klimatologi

Glopeflya: Fimbulheimen (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Hoelfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

On the radiation balance and micrometeorological conditions at Norway station, Antarctica - Vinje, Torgny E (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; meteorologi; stråling

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Cooling effect of an Antarctic climate on man : with some observations on the occurence of frostbite - Wilson, Ove (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; forfrysning; klima; medisin

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Filchnerfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1962)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Sör: Fimbulheimen (Norsk Polarinstitutt, 1962)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Note on occurence of limburgite in Dronning Maud Land, Antarctica - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1960, 1962)
The rocks from Dronning Maud Land, collected by T. LUNDE along 72° S and between 3° W and 7° E are mostly ordinary gneisses. However, a black, basaltic rock, apparently belonging to a sil! or a dyke has been found on Jutulsessen. The rock is lacking feidspar and consists only of augite, olivine, devitrified glass, and accessories. The chemical composition of the rock, mode and norm are given in table I. The present investigation shows that the Antarctic limburgite seems to be related to the normal olivine basalts, and not to the derivates of the basanite series.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi

Notes on the geology and petrology of the mountains in Fimbulheimen, Dronning Maud Land - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1961, 1962)
On the coastal slope of the great inland ice of Dronning Maud Land, Antarctica, a number of mountain peaks rises above the ice cap. The central part of the nunatak area consists of very coarse grained hornblende-biotite granite, poor in quartz and rich in porphyroblastic microcline crystals. It is cut by foliated or banded gneisses consisting essentially of the same minerals. The granite clearly intersects the gneiss, and both are cut by more fine-grained granite veins as well as by pegmatite. In some places the gneiss contains red garnet crystals, hut with one possible exception it is not proper chamockite.
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; geologi; petrologi

Absolute age determinations on rocks from Dronning Maud Land - Heintz, Natascha; Siggerud, Thor (Norsk Polarinstitutt. Årbok 1960, 1962)
Age determinations made by Belgian, Japanese and Soviet-Russian scientists on rocks from Dronning Maud Land, Antarctica are referred. These age determinations, done by different methods all indicate an age of about 500 million years for the last orogeny in this area, a result already expected on bases of geological evidence from other areas.
Keywords: Dronning Maud Land; geologi

The volume of ice in Antarctica - Liestøl, Olav (Norsk Polarinstitutt. Årbok 1961, 1962)
At present c. 15 mill. km• of the earth's surface is covered with ice. Of this area about 85 % falls to the account of Antarctica, 11 % to Greenland and c. 4 % to other areas. From this it is evident that a good knowledge of the ice mass of Antarctica is a deciding factor for the calculation of the total ice volume on earth and its effect on eustatic changes.
Keywords: Dronning Maud Land; glasiologi; havis; havnivåstigning; sjøis

Maudheim Revisited: The Morphology and Regime of the lce Shelf, 1950-1960 - Swithinbank, Charles (Norsk Polarinstitutt. Årbok 1960, 1962)
Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition, 1949-52, (71° 02' S, 10° 56' W) was revisited in January 1960 by the Norwegian Antarctic Expedition, 1956-60 under the leadership of SIGURD HELLF.. HELLE has very kindly made his observations available to me and has read the manuscript of this note. The work of his party gives a reliable measure of the accumulation of snow at Maudheim from 1952 to 1960 and allows a hetter estimate of the bottom melting on the ice shelf than was possible from the 1950-52 measurements. Air photographs taken in December 1958 by B. LuNCKE show the extent of changes in the ice front since 1951.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The cooling power in Antarctica - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1961, 1962)
We have measured the cooling power at Norway Station (70°.5 S, 2°.5 W)with kata-thermometers for air-temperature (Ta) between + 1 and --41° C, and for wind speeds (v) at 10 m leve! up to 27 m sec-1• The linear proportionality of the cooling power (H) to (36.5-Ta), for a constant wind speed, is shown to hold in this temperature-interval for a wind speed less than about 12 m sec-1• We used four kata-thermometers, and it turned out that they gave systematic different values of the cooling power for equal meteorological conditions. Comparing the individual values with their mean we find a maximum deviation of about ± 20 % . W e have supposed that this is due to errors in the calibration, subjective errors plus dissimilarities in the shape of the bulbs. The latter will cause differences in the turbulence around the bulbs, and consequently in the effective cooling of the wind. The possible difference in the cooling power of the air due to differences in the shape will probably not emerge during calibrations in a still air chamber. In spite of the dissimilar climatic conditions in Antarctica and Europe we found that a formula based upon two of our Katas, with which we have taken by far the most measurements, corresponds fairly well to the mean of the Kata-formulae found in Europe. The maximum deviation of the values given by European formulae from those derived by the Norway Station formula is about ± 20 %. We have here omitted the formula of HILL (1919), as it reveals a fairly large deviation from the other formulae.
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; meteorologi

Basal metabolic rate of “tropical” man in a polar climate - Wilson, Ove (Biometeorology: Proceedings of the Second International Bioclimatological Congress Held at the Royal Society of Medicine, London, 4–10 Sept. 1960, Organized by "The International Society of Biometeorology", 1962)
Naked man in his mode of heat regulation can be regarded as a tropical or subtropical creature with a narrow zone of adaptability, and the difference in the BMR determined in the tropics and in a temperate zone for the same individuals does not seem to exceed 10 per cent. In the climatic extremes he raises his calorific output in situations of stress but does not adapt by further changing his BMR. Some native people, however, appear to have the ability to endure a moderate cold stress without increasing their heat production above normal basal values. The metabolic determinations made by the author on the Norwegian—British–Swedish Expedition during 2 years of continuous exposure to the Antarctic climate show that there is no difference in the mean level of the BMR of white man whether he lives in a temperate or a polar climate. Other studies in cold regions support this view. Evidence of acclimatization of man to cold will not be found in the basal metabolic rate. However, the author's investigations show that the polar climate in its extreme form, as it is encountered by man in the Antarctic, can impose certain seasonal variations in the BMR. This periodicity in BMR is probably not a direct effect of climate on metabolism, but is related to it by reason of the typical activity pattern which ensues in the Antarctic climate. In agreement are the seasonal changes in BMR in the Arctic reported by Russian workers. The preliminary results of Lewis and Masterton in North Greenland, on the other hand, do not indicate a consistent seasonal variation. In changing from a temperate to a tropical climate, the BMR may vary within a narrow range of about 10 per cent, decreasing in the hot environment, but not all persons will show such a change. The seasonal variation found by the author in a polar climate is almost of the same order as the change in the tropics. It may be that the alterations in BMR caused by a change to a tropical climate are due to similar influences, which, however, do not exhibit the same seasonal incidence, because of the uniformity of the climate the year around. This implies that the basal metabolism of white man is essentially the same in all climates, but varies within a narrow range, not as a direct result of climate itself or its mean temperature, but depending upon changes in the type of activity, food, exposure, muscle tone and other factors, which are imposed by a difference in climate and regimen.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Ahlmannryggen: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

H.U.Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Kirwanveggen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Neumayerskarvet: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

On the snow accumulation in Dronning Maud Land - Lunde, Torbjørn (Norsk Polarinstitutt, 1961)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; morfologi; observasjoner; snø

The snow petrel Pagodroma nivea nesting in Dronning Maud Land - Løvenskiold, Herman L. (Ibis, 1960)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Noteveksling mellom Norges regjering og Sør-Afrika-Sambandets regjering angående lån til Sør-Afrika-Sambandet av Norway Station beliggende i det norske biland Dronning Maud Land - Utenriksdepartementet (Statsrådsekretariatet, 1960)
Keywords: Dronning Maud Land; jus; politikk; stasjoner

Otter'n, sprækeste fly i verden: skjeggete Antarktis-flygere hjemme igjen etter vellykket kartlegging av norske ismasser - Heyerdahl, Johan Fredrik (Mannskapsavisa, 1959)
Keywords: Dronning Maud Land; ekspedisjoner; fly; kartlegging; logistikk

Vitenskap i kaldt land (Aktuell, 1958)
Keywords: Dronning Maud Land; ekspedisjoner

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

Determination of the Thickness of Ice Shelves by Seismic Shooting Methods - Robin, Gordon de Quetteville (Nature, 1956)
SEISMIC soundings of the thickness of the floating ice shelves of Antarctica have so far been attempted by two expeditions, the Second Byrd Antarctic Expedition of 1933–35 1, and the Norwegian–British–Swedish Antarctic Expedition 1949–52 2,3. Further measurements are likely to be made by several expeditions during the International Geophysical Year 1957–58. Reinterpretation of results from iceshelves obtained from the Norwegian-British-Swedish Antarctic expedition 1949-52.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Upper Air Temperatures over an Antarctic Station: A preliminary note by - Schumacher, Nils Jørgen (Tellus, 1955)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Sledge dogs of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1954)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; sledehunder

Measurements of ice thickness in Dronning Maud Land - Robin, Gordon de Quetteville (Polar Record, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Landmålerliv i Dronning Maud Land - Roer, Nils (Brøggers forlag, 1954)
Keywords: Dronning Maud Land; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; kartografi; landmåling

The base of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An International Expedition to Antarctica - Robin, Gordon de Quetteville (The Geographical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Measurements of Ice thickness in Dronning Maud Land, Antarctica - Robin, Gordon de Quetteville (Nature, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; glasiologi

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Robin, Gordon de Quetteville (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Preliminary note on the geology of western Dronning Maud Land - Roots, Ernest Frederick (Brøggers forlag, 1953)
Keywords: Dronning Maud Land; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi

The currents of the coast of Queen Mauds Land - Sverdrup, Harald Ulrik (1953)
Keywords: Dronning Maud Land; glasiologi; havstrømmer; isshelf

Mechanical Transport of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Swithinbank, Charles (Polar Record, 1953)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Er det noen forskjell mellom Arktis og Antarktis? - Giæver, John (Magasinet for alle, 1952)
Keywords: Dronning Maud Land; ekspedisjoner

Maudheim : to år i Antarktis : den norsk-britisk-svenske vitenskapelige ekspedisjon til Antarktis 1949-1952 - Giæver, John (Gyldendal, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Antarktis, der snøfokket pisker i juli : om ismassene rundt Sydpolen smelter, stiger verdenshavene med 30 meter : "Norsel"-ekspedisjonen får stor betydning for vitenskapen - [Roer, Nils] (Nå, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; Sydpolen; vitenskap

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1951)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Die Norwegisch-Britisch-Schwedische Expedition in die Antarktis - Sverdrup, Harald Ulrik (Polarforschung, 1951)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The International Expedition to Queen Maud Land (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Roberts, Brian Birley (Polar Record, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Norwegian-British-Swedish Expedition to Queen Maud Land (The Geographical Journal, 1949)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1949)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Preliminary Glaciological Plans for the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Ahlmann, Hans Wilhelmsson (Journal of Glaciology, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The Norwegian-Swedish-British Antarctic Expedition - Ahlmann, Hans Wilhelmsson (Tellus, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Dronning Mauds Land - Giæver, John (Magasinet for alle, 1949)
Keywords: Dronning Maud Land; ekspedisjoner

The Antarctic Continent - Law, Phillip Garth (Walkabout, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Norwegian-British-Swedish expedition to the Antarctic (The Geographical Journal, 1948)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Norwegian-British-Swedish Expedition to the Antarctic (The Geographical Journal, 1948)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Proposed British-Norwegian-Swedish Antarctic Expedition, 1948–50 (Polar Record, 1947)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Contemporary International Interest in the Antarctic - Fleming, W L S (International Affairs, 1947)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Entdeckungen und Ansprüche in der Antarktis - Drygalski, Erich von (Geographische Zeitschrift, 1944)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; internasjonal; polarhistorie; politikk

Oppdeling av polatraktene - Hoel, Adolf (Norge i Ishavet, 1941)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; internasjonal politikk; polarområdene

Norsk statsvelde i Antarktis - Utenriksdepartementet (1939)
Keywords: Dronning Maud Land; historie; politikk; statsvitenskap

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning